European Erasmus Programme: Main Stages and Results of Development (1987-2017) - O. N. Bogatyryova; N. V. Leskina (Научный диалог)
The article is devoted to the evolution of the flagship educational programmes of the European Union ERASMUS and its impact on the Europeanization of higher education. The development of academic mobility and exchange programmes, joint educational programmes, as well as transnational University networks are discussed. Special attention is paid to the analysis of the historical context and the reasons for its formation, main stages of development and the impact it has had on European integration in higher education. The basic stages of development of the ERASMUS programme are considered, their contents and features of the transformation of the programme are shown. The authors come to the conclusion that, although the first evaluation of the programme considering its contribution to the development of European identity and career prospects of graduates was a little high, it finally contributed to the cooperation between universities and to strengthening of transnational academic community, which was interested in further expansion of supranational regulation and contributed to the strengthening of the powers of the EU in this field. It is noted that it has become a platform for testing collaborative tools, which were later enshrined in the provisions of the Bologna Declaration. It is underlined that the ERASMUS programme has become one of the sources of funding for the Bologna reforms.